Enhanced Pulmonary Vasodilator Reserve and Abnormal Right Ventricular. (May 2015) - Andersen, Mads J.; Hwang, Seok-Jae; Kane, Garvan C.; Melenovsky, Vojtech; Olson, Thomas P.; Fetterly, Kenneth; Borlaug, Barry A.
<x xml:space="preserve">Abstract</x> Background— Pulmonary hypertension and right ventricular (RV) dysfunction are common in patients with advanced heart failure with preserved ejection fraction (HFpEF), yet their underlying mechanisms remain poorly understood. We sought to examine RV–pulmonary artery (PA) functional reserve responses and RV–PA coupling at rest and during β-adrenergic stimulation in subjects with earlier stage HFpEF. Methods and Results— In a prospective trial, subjects with HFpEF (n=39) and controls (n=18) underwent comprehensive invasive and noninvasive hemodynamic assessment using high fidelity micromanometer catheters, echocardiography, and expired gas analysis at rest and during dobutamine infusion. HFpEF subjects displayed similar RV structure but significantly impaired RV systolic (lower RV dP/dtmax/IP and s′) and diastolic function (higher RV τ) coupled with more severe pulmonary vascular disease, manifest by higher PA pressures, higher PA resistance, and lower PA compliance compared with controls. Dobutamine infusion caused greater pulmonary vasodilation in HFpEF compared with controls, with enhanced reductions in PA resistance, greater increase in PA compliance, and a more negative slope in the PA pressure–flow relationship when compared with controls (all P<0.001). RV–PA coupling analysis revealed that dobutamine improved RV ejection in HFpEF subjects through afterload reduction alone, rather than through enhanced contractility, indicating RV systolic reserve dysfunction. Conclusions— Pulmonary hypertension in early stage HFpEF is related to partially reversible pulmonary vasoconstriction coupled with RV systolic and diastolic dysfunction, even in the absence of RV structural remodeling. Pulmonary vascular tone is more favorably responsive to β-adrenergic stimulation in HFpEF than controls, suggesting a potential role for β-agonists in the treatment of patients with HFpEF and pulmonary hypertension. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT01418248.